Early diagnosis and management of dementia in general practice – how do Swiss GPs meet the challenge? - Stéphanie Giezendanner; Andreas U. Monsch; Reto W. Kressig; Yolanda Mueller; Sven Streit; Stefan Essig; Andreas Zeller; Klaus Bally (Swiss Medical Weekly, 2018)
INTRODUCTION